Violent conflict and ethnicity in the Congo: beyond materialism, primordialism and symbolism. Issue 5 (2nd September 2020) - Hoffmann, Kasper; Vlassenroot, Koen; Carayannis, Tatiana; Muzalia, Godefroid
ABSTRACT: In this paper, we investigate the nexus between ethnicity and violent conflict in the Congo. We make three interlocking arguments. First, we argue that ethnicity is a defining political resource in the Congo's politics and violent conflicts, which we call 'ethnic capital'. Second, we argue that the high political value of this ethnic capital is sustained by engrained discourses and practices of ethnicity. These discourses and practices permeate the Congo's political order, shape people's understanding of politics, conflict and political identities, and have contributed to the formation of an unstable, centrifugal, and fragmentary political order. Third, we argue that conceptualising ethnicity as capital dismantles the artificial dualism between the symbolic realm of identities and the material realm of the economy and makes it possible to move beyond primordialist, instrumentalist and purely symbolic understandings of the nexus between conflict and ethnicity. Ultimately, what is at stake in this competition is the distribution of symbolic and material resources.